2021
DOI: 10.3390/jcm10132895
|View full text |Cite
|
Sign up to set email alerts
|

Is Shear-Wave Elastography a Clinical Severity Indicator of Myofascial Pain Syndrome? An Observational Study

Abstract: Since manual palpation is a subjective procedure for identifying and differentiate Myofascial Trigger Points -MTrPs-, the use of Shear Wave Elastography -SWE- as an objective alternative is increasing. This study aimed to analyze pain pressure thresholds -PPTs- and SWE differences between active MTrPs, latent MTrPs and control points located in the upper trapezius to analyze the association of SWE features with clinical severity indicators (e.g., pain extension area, PPTs, neck pain and neck disability). An ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
1
32
3
Order By: Relevance
“…A physiotherapist, with 10 years of experience and an expert in musculoskeletal imaging, used the Logiq S7 with 15 MHz linear probe (GE Healthcare, Milwaukee, WI, USA) to carry out measurements on the subjects following the orientation guidelines used for tender point recognitions [ 41 ]. Given that the longitudinal plane demonstrated both a higher intra- and inter-examiner reliability (ICC = 0.66–0.74) than the transversal one [ 42 ], the transducer was positioned longitudinally to the muscle fibers with the center of the probe over the tender and control point locations and approximately 2–5 mm of compression was applied to the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…A physiotherapist, with 10 years of experience and an expert in musculoskeletal imaging, used the Logiq S7 with 15 MHz linear probe (GE Healthcare, Milwaukee, WI, USA) to carry out measurements on the subjects following the orientation guidelines used for tender point recognitions [ 41 ]. Given that the longitudinal plane demonstrated both a higher intra- and inter-examiner reliability (ICC = 0.66–0.74) than the transversal one [ 42 ], the transducer was positioned longitudinally to the muscle fibers with the center of the probe over the tender and control point locations and approximately 2–5 mm of compression was applied to the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, since there are multiple imaging modes based on US technologies, multiple parameters can be easily and objectively assessed. For instance, the Doppler mode is useful for assessing vascular flows (facilitating the identification of vascular structures or assisting with the interventions’ effects on these vessels) [ 5 ], the M-mode assists with analyzing thickness changes in real-time (especially useful during motor control exercises if patients need feedback to ensure a correct muscle activation) [ 6 ], shear-wave elastography allows an objective assessment of a tissue’s stiffness [ 7 ] and panoramic US allows the measurement of large structures not measurable with conventional B-mode images [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study conducted by Jafari et al [33] assessed MTrP stiffness by using elastography imaging to quantitatively distinguish MTrP from normal tissue and obtained significant differences between MTrPs and the normal part of the muscle. However, a recent study found no stiffness differences between active and latent MTrPs or control points with MTrPs [12]. The methodology assessed on this study could be applied to calculate the SR between an MTrP control point or two control points (since it showed a good validity and reliability), its correlation with pain pressure thresholds and SR changes after treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Although previous studies have assessed utility aspects of semi-quantitative strain elastography to calculate SR, most studies tackled references and targets with significant stiffness differences [8,9,11,13]. However, recent research focusing on MTrPs demonstrated that the magnitudes of stiffness differences in real tissues are smaller than the ones analyzed in phantoms [12]. As previous reports demonstrated that the accuracy of strain elastography is directly proportional to the stiffness difference between two points, the main novelty of this study lies in the selection of a homogeneous material to calculate the reliability between examiners and the instrument validity considering the region of interest location and the experience of the examiners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation